2004
DOI: 10.1080/0376835042000265478
|View full text |Cite
|
Sign up to set email alerts
|

Farmers' cash crop cultivation decisions in Southern Niassa province, Mozambique

Abstract: The aim of this study was to evaluate socially farmers' decisions about the cultivation of cash crops. It specifically assessed the feasibility of World Relief-SempreVerde scheme by investigating the agricultural promoters; the factors influencing farmers' decisions to adopt, reject, discontinue or continue with the promoted crops; and the support required for improving the food and income security of smallholder farmers. The research took place in nine villages in Cuamba district, Niassa province, Mozambique.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…This indicator can predict the possible preferences for a promoted cash crop or crops above food cash crops. In the 2000/01 season, when the JFS Company was at an early stage of introducing tobacco in southern Niassa, more than 63 per cent of the respondents sold food cash crops while only 21 per cent sold tobacco (Lukanu et al, 2004). In the following agricultural season, with awareness and knowledge about the high profitability of tobacco, the total percentage of respondents participating in the marketing of food cash crops dropped to 38 per cent while that for tobacco increased to 40 per cent.…”
Section: Ratio Between Profit2 Of Promoted Cash Crops and Food Cash Cmentioning
confidence: 90%
See 3 more Smart Citations
“…This indicator can predict the possible preferences for a promoted cash crop or crops above food cash crops. In the 2000/01 season, when the JFS Company was at an early stage of introducing tobacco in southern Niassa, more than 63 per cent of the respondents sold food cash crops while only 21 per cent sold tobacco (Lukanu et al, 2004). In the following agricultural season, with awareness and knowledge about the high profitability of tobacco, the total percentage of respondents participating in the marketing of food cash crops dropped to 38 per cent while that for tobacco increased to 40 per cent.…”
Section: Ratio Between Profit2 Of Promoted Cash Crops and Food Cash Cmentioning
confidence: 90%
“…Their decisions are influenced more by the risk factors or the pragmatic aspects of profitability than by the financial aspects. For example, Lukanu et al (2004) found that a reliable buyer was the second most important factor that made smallholders decide to cultivate and market particular crops in southern Niassa. They will not cultivate a cash crop if the marketing system is unlikely to absorb their output (Hornik, 1993).…”
Section: Theoretical Backgroundmentioning
confidence: 98%
See 2 more Smart Citations
“…Two earlier studies identified labour as one of the most important factors influencing smallholders' decision to cultivate cash crops. Lukanu et al (2004) identified, in order of importance: (i) profitability, (ii) market access, (iii) availability of inputs and implements, (iv) labour, and (v) access to extension services; and Green et al (2006) reported that the number of effective labourers was the most determining factor that explained variation in market participation. Makhura (2001) also found that labour factors influenced smallholders' participation in agricultural markets.…”
Section: Introductionmentioning
confidence: 98%